Penggunaan Strategi Pembelajaran Berbasis Masalah dalam Peningkatan Motivasi Belajar dan Hasil Belajar Pendidikan Agama Islam Siswa - Raja Tambunan (UIN SYEKH ALI HASAN AHMAD ADDARY PADANGSIDIMPUAN, 2020)
This research is a class action research conducted collaboratively. In its implementation the researchers used problem-based learning strategies in increasing student motivation and learning outcomes on Islamic economic principles and practices. This class action research was carried out in 3 cycles. The results of this study indicate that the use of problem-based learning strategies can increase student motivation and learning outcomes in Islamic Religious Education. In the pre-action based on the observation sheet of student learning motivation is an average value of 48.16%, in the first cycle 55.90%, second cycle 65.90%, while the third cycle 88.71%. The learning outcomes of Islamic Religious Education students in pre-action is with an average grade of 75, in the first cycle the average value of the class 79.03, in the second cycle the average value of the class 82.25, in the third cycle all students already have a complete value with an average value of 88.06